Financial dollarization and business cycle uncertainty - KIZIR, Jonathan (KDI School, 2017)
This thesis estimates the stochastic relationship between financial dollarization and business cycle uncertainty using quantile regression technique over the period 2000 to 2015. We do not find strong evidence of a significant effect of business cycle uncertainty on financial dollarization in the Democratic Republic of the Congo. Inflation negatively affects dollarization from lower quantiles to higher quantiles. However, the effect is statistically insignificant. The oil price index has a positive influence on dollarization but the effect is statistically insignificant as well. Other control variables have no significant effect on dollarization (net exports, investment and government consumption). We attribute dollarization hysteresis in DRC to a memory effect in economic agent’s mind: lack of trust in monetary authorities due to past hyperinflation and macroeconomic instability back in the 1990s and the early 2000s. We also attribute dollarization inertia to positive network externalities. Constant exchange rate depreciation is another cause of dollarization hysteresis. On top of all, political instability in DR Congo is a serious cause of dollarization inertia. We recommend a sustainable dedollarization process in DRC.
Thesis(Master) --KDI School:Master of Public Policy,2017